Symptoms of Mental Health Problems: Children’s and Adolescents’ Understandings and Implications for Gender Differences in Help Seeking - MacLean, Alice (Child Soc, 2013)
Amidst concerns that young people’s mental health is deteriorating, it is important to explore their understandings of symptoms of mental health problems and beliefs around help seeking. Drawing on focus group data from Scottish school pupils, we demonstrate how they understood symptoms of mental health problems and how their characterisations of these symptoms as ‘rare’ and ‘weird’ informed participants’ perceptions that peers, teachers and parents would respond to disclosure in stigmatising ways. Consequently, participants suggested that they would delay or avoid disclosing symptoms of mental health problems. We highlight subtle gender and age differences and outline implications for policy and practice.